Acute Simian Immunodeficiency Virus Infection Triggers Early and Transient Interleukin-7 Production in the Gut, Leading to Enhanced Local Chemokine Expression and Intestinal Immune Cell Homing - Ponte, Rosalie; Rancez, Magali; Figueiredo-Morgado, Suzanne; Dutrieux, Jacques; Fabre-Mersseman, Véronique; Charmeteau-de-Muylder, Bénédicte; Guilbert, Thomas; Routy, Jean-Pierre; Cheynier, Rémi; Couëdel-Courteille, Anne (Frontiers in Immunology, 2017)
The intestinal barrier, one of the first targets of HIV/SIV is subjected to major physiological changes during acute infection. Having previously shown that pharmaceutical injection of interleukin-7 (IL-7) triggers chemokine expression in many organs leading to massive T-cell homing, in particular to the intestine, we here explored mucosal IL-7 expression as part of the cytokine storm occurring during the acute phase of Simian Immunodeficiency Virus (SIV) infection in rhesus macaques. Quantifying both mRNA and protein in tissues, we demonstrated a transient increase of IL-7 expression in the small intestine of SIV infected rhesus macaques, starting with local detection of the virus by day 3 of infection. We also observed increased transcription levels of several chemokines in the small intestine. In infected macaques, ileal IL-7 expression correlated with the transcription of four of these chemokines. Among these chemokines, the macrophage and/or T-cell attractant chemokines CCL4, CCL25 and CCL28 also demonstrated increased transcription in uninfected IL-7-treated monkeys. Through immunohistofluorescence staining and image analysis, we observed increased CD8+ T-cell numbers and stable CD4+ T-cell counts in the infected lamina propria during hyperacute infection. Concomitantly, circulating CCR9+beta7+ CD4+ and CD8+ T-cells dropped during acute infection, suggesting augmented intestinal homing of gut-imprinted T-cells. Finally, CD4+ macrophages transiently decreased in the submucosa and concentrated in the lamina propria during the first days of infection. Overall, our study identifies IL-7 as a danger signal in the small intestine of Chinese rhesus macaques in response to acute SIV infection. Through stimulation of local chemokine expressions, this overexpression of IL-7 triggers immune cell recruitment to the gut. These findings suggest a role for IL-7 in the initiation of early mucosal immune responses to SIV and HIV infections. However, IL-7 triggered CD4+ T-cells and macrophages localization at viral replication sites could also participate to viral spread and establishment of viral reservoirs.